Weight training steps to success - Baechle, Thomas R. 1943-; Groves, Barney R. 1936- (Steps to success activity series, 2012)
Combining the experience of strength and conditioning experts Thomas Baechle and Roger Earle, this guide will maximize your development with a progressive approach to weight training using either free weights or machines. Learn which exercises target which muscles and how to perform each one correctly and safely. Gain insight on how to eat smart to maximize results and follow the step-by-step directions to calculate safe training loads and design an overall training program that fits your interests and training preferences